Efficacy of Levofloxacin Loaded Nonionic Surfactant Vesicles (Niosomes) in a Model of Pseudomonas aeruginosa Infected Sprague Dawley Rats - Satish Jankie; Jenelle Johnson; Amusa Sarafadeen Adebayo; Gopal Krishna Pillai; Lexley Maureen Pinto Pereira (Hindawi Limited, 2020)
This study examined the effectiveness of niosomes loaded with levofloxacin in treating Pseudomonas aeruginosa (American Type Culture Collection-ATCC 27853) infections in Sprague Dawley rats since these infections are becoming more common and resistant to treatment. Levofloxacin entrapped in niosomes was prepared using the thin-film hydration method and was assessed for in vitro release and stability. Three groups of six (6) animals were infected with a lethal dose of Pseudomonas aeruginosa via the intraperitoneal (Ip) route. At six (6) hours postinfection, the animals were treated with either drug-free niosomes (control), free levofloxacin (conventional), or levofloxacin trapped in niosomes (Ip) at a dose of 7.5 mg/kg/once daily. Blood was collected via tail snips on days 0, 1, 3, 5, 7, and 10 for complete blood counts and viable bacterial counts (CFU/μl). At day 10, the animals were sacrificed, and the kidney, liver, and spleen were harvested for bacterial counts. The niosomes showed a sustained drug release profile and were most stable at 4°C. All animals in the control group succumbed to the infection; one animal from the conventional group died, and all niosome treated animals survived at day 10. The mean lymphocyte count (×109) was lower for the niosome (7.258 ± 1.773) versus conventional group (17.684 ± 10.008) (p<0.03) at day ten (10). Neutrophil counts (×109) were lower for the niosome (2.563 ± 1.609) versus conventional (6.2 ± 6.548) (p<0.02) groups. Though CFUs in the bloodstream were comparable for both treatment groups, the niosome treated group showed a significant reduction of CFUs in the liver, kidney, and spleen versus the conventional group (1.33 ± 2.074) vs (5.8 ± 3.74) (p<0.043), (1.5 ± 2.35) vs (9.6 ± 8.65) (p<0.038) and (3.8 4.71) vs (25.6 14.66) (p<0.007), respectively. These findings indicate that niosome is promising as a drug delivery system in treating systemic infections, but further work using niosomes with surface modification is recommended.